Effect of Liquid Hot Water Pretreatment on Hydrolysates Composition and Methane Yield of Rice Processing Residue - Lisbet Mailin López González; Monika Heiermann (Energies, 2021)
Lignocellulosic rice processing residue was pretreated in liquid hot water (LHW) at three different temperatures (140, 160, and 180 °C) and two pretreatment times (10 and 20 min) in order to assess its effects on hydrolysates composition, matrix structural changes and methane yield. The concentrations of acetic acid, 5-hydroxymethylfurfural and furfural increased with pretreatment severity (log Ro). The maximum methane yield (276 L kg−1 VS) was achieved under pretreatment conditions of 180 °C for 20 min, with a 63% increase compared to untreated biomass. Structural changes resulted in a slight removal of silica on the upper portion of rice husks, visible predominantly at maximum severity. However, the outer epidermis was kept well organized. The results indicate, at severities 2.48 ≤ log Ro ≤ 3.66, a significant potential for the use of LHW to improve methane production from rice processing residue.